Effectiveness of current protein recommendations in adolescent athletes on a low-carbon diet - Franca, Paula Albuquerque Penna; Gonçalves Lima, Christine Katharine Alves Zago; Oliveira, Taillan Martins de; Ferreira, Tathiany Jéssica; da Silva, Renata Romanelli Mollini; Loureiro, Luiz Lannes; Pierucci, Anna Paola Trindade Rocha (Frontiers in Nutrition, 2022)
Adolescent athletes require adequate energy and nutrient supply to support growth, development, and the demands associated with exercise and training. However, they are susceptible to nutritional inadequacies affecting their health and physical performance. Food choices with nutrient adequacy and environmental protection is crucial for a sustainable diet. Therefore, we aimed to assess the adequacy of low-carbon diets to meet the protein requirements of adolescent athletes. Therefore, a cross-sectional observational study was conducted with 91 adolescent athletes from sports clubs in Rio de Janeiro who underwent anthropometric and food consumption assessments. To estimate the environmental impact of anthropogenic activities, the sustainability indicators carbon footprint (CF) and water footprint (WF) were used. The CF of the athlete’s diet was compared with the benchmark of 1,571 g CO2eq/cap/d estimated by the World Wildlife Fund (WWF). Protein recommendations according to the American Dietetic Association (ADA) for athletes and protein food groups according to the low-carbon EAT-Lancet reference diet were used as references. The results were stratified by sport modality, age, sex, and income range. The Mann-Whitney test was performed, followed by the Kruskal-Wallis test with Dunn's post-hoc test to assess the differences between groups using the statistical program GraphPad PRISM®️ version 8.0. CF and WF were directly associated with total energy intake, total protein intake, animal-origin protein intake, and the food groups of meat and eggs. Significant differences were observed in the environmental impact of diet based on sports groups and gender. The athletes’ profile with higher environmental impact was male, middle-income class, and of any age group. The quartiles of CF of the overall diets were above the 1,571 g CO2eq/cap/d benchmark. Additionally, ADA´s recommended range of daily protein consumption was met by most athletes, even in the lowest quartile of CF. Thus, a diet with a lower environmental impact can meet protein recommendations in adolescent athletes. The results found are of interest to the sports and food industries. It could help in designing a balanced diet for athletes as well as ensure less negative environmental impacts of food production and consumption.